2018
DOI: 10.1111/jmp.12378
|View full text |Cite
|
Sign up to set email alerts
|

Determination of baseline values for routine ophthalmic tests in bearded capuchin (Sapajus libidinosus)

Abstract: Determination of baseline values for eye measurements and ophthalmic tests will assist in the diagnosis of eye diseases in S. libidinosus monkeys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
1
5
1
Order By: Relevance
“…39,40 In addition, bearded capuchins (Sapajus libidinosus) also have been reported to have relatively low tear production (2.5 ± 2.94 mm/min), speculatively attributed to the use of detomidine in addition to ketamine in the anesthetic protocol. 41 Age was found to be unrelated to STT values in the only other prior NHP study that used age as a variable, 37 in contrast to our results which showed that JAGM had significantly lower tear production than AAGM or GAGM. However, the aforementioned study had a relatively small sample size of 15 primates from ages 6 to 20 years old, which excludes comparison to a juvenile group.…”
Section: F I G U R Econtrasting
confidence: 90%
“…39,40 In addition, bearded capuchins (Sapajus libidinosus) also have been reported to have relatively low tear production (2.5 ± 2.94 mm/min), speculatively attributed to the use of detomidine in addition to ketamine in the anesthetic protocol. 41 Age was found to be unrelated to STT values in the only other prior NHP study that used age as a variable, 37 in contrast to our results which showed that JAGM had significantly lower tear production than AAGM or GAGM. However, the aforementioned study had a relatively small sample size of 15 primates from ages 6 to 20 years old, which excludes comparison to a juvenile group.…”
Section: F I G U R Econtrasting
confidence: 90%
“…The IOP results from Guianan squirrel monkeys were lower than the IOP for the black-tufted marmosets and the night monkeys. Values for the two last species are more closely related to the IOP values reported for New World NHP including 18.4 ± 3.8 mmHg for Cebus apella 13 ; 19 ± 4 mmHg for Sapajus xanthosternos 16 ; 13 ± 3 mmHg for Sapajus libidinosus 2 , and 13 ± 1 mmHg for Aotus trivirgatus . 9,20 This relatively low value for Guianan squirrel monkeys requires more investigation to determine the reason for this difference.…”
Section: Discussionsupporting
confidence: 69%
“…The Cochet-Bonnet esthesiometer gauges the longest length of a nylon filament of 0.08 mm in diameter, causing nociception when in contact with the cornea. The CTT is inversely proportional to the magnitude of measurement in filament length (cm) and its pressure applied on the corneal surface (g/mm 2 ). On the day the data from Guianan squirrel monkeys and night monkeys were acquired at CENP, Ananindeua, Pará, Brazil, mean temperature was 32° and mean humidity 58%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 However, in non-human primates, few reports are found and are not associated with a specific disease, but with infections caused by opportunistic bacteria. Research by Bezerra et al 28 and Silva 29 carried out with Sapajus spp. free of clinical conditions detected Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%